Effect of a hydrotherapy based alternate compress on osteoarthritis of the knee joint: a randomized controlled trial - T., Archanah; H. C., Shashikiran; Shetty, Prashanth; K. K., Chandrakanth (International Journal of Research in Medical Sciences, 2018)
Background: Osteoarthritis (OA) of the knees causes pain; swelling and decreases its range of motion in the knee joint. An alternate hot and cold compress gives a circulatory effect without thermic reaction. This treatment induces only a revulsive, non-excitant, and analgesic effect, till date there have been no investigations on the usage of an alternate hot and cold compress as an intervention in individuals with OA of knees. Methods: The control group (n=30) received only routine naturopathy based treatments, whereas the study group received naturopathy based treatments along with an alternate hot and cold compress as an additional intervention for 10 days. Subjects were assessed with Numerical Rating Scale (NRS) and Knee injury and Osteoarthritis Outcome Score (KOOS) as standard questionnaires at baseline and at the end of 10 days. Results: To perform statistical analysis of the collected data we use Kolmogorov-Smirnov goodness of fit test to validate the assumption of normality. We applied Paired sample t – test to test the effectiveness before the treatment and after the treatment in Control group as well in Intervention group. We use independent two sample t-test to test effectiveness of treatment. Results of NRS and KOOS questionnaire are expressed as mean and standard deviation and P value (< 0.05). There was a significant reduction in pain in experimental group compared to control group P value (< 0.05). Conclusions: This study concluded that an alternate hydryatic compress was effective in the management of pain in knee OA.